Effects of maternal anaemia on neonatal outcome a study done in the specialized urban hospital set up in Bangladesh - Mahamuda, B; Tanira, S; Feroza, W; Perven, HA; Shamim, A (Bangladesh Journal of Medical Science, 2011)
Context: Anaemia is a common pregnancy related disorder in Bangladesh that causes various maternal and fetal problems. A prospective study was designed to see the associated maternal factors and fetal outcome in different categories of anaemia and to compare with that of normal pregnancy. Methods: The study was carried out on 60 Bangladeshi women within 35-40 weeks of gestation. Among them, 20 with normal uncomplicated pregnancies were considered as control group or group A, another 27 having pregnancies with mild anaemia were considered as group B, and 13 having pregnancies with moderate anaemia were considered as group C. Severe anaemic mothers were considered as group D, but not found during the period of collection of data for this study. The mothers were selected as who were suffering from antenatal anaemia i.e. having heamoglobin level <10 gm/dl (mild, if <10 gm/dl; moderate, if <8 gm/dl; and severe, if <6 gm/dl) and control i.e. having heamoglobin level ≥10 gm/dl. The foetal outcome was observed and recorded after delivery. Results: The mean age of the mother was 23.65±3.83 years, 27.26±4.93 years and 25.85±4.62 years and the mean number of gravidity was 1.65±0.67, 2.15±0.72 and 2.69±1.03 in group A, group B and group C respectively. The difference was statistically highly significant in between A and C (p<0.001) and also significant in between A & B and B & C (p<0.05). The mean gestational age of the mother was 38.65±0.88 weeks, 37.37±1.01 weeks and 37.15±1.28 weeks in group A, group B and group C respectively and the difference was statistically significant between A & B and A & C (p<0.001). The mean birth weight of the neonate was 3.09±0.30 Kg., 2.99±0.16 Kg. and 2.95±0.21 Kg., while the mean APGAR score of the neonate at first minute of birth was 8.90±1.07, 8.11±0.89 and 7.69±0.48 in group A, group B and group C respectively. No significant difference was found in birth weight of the newborn babies in between the groups of the mothers. However, the difference was found significant in between A & B (p<0.01) and A & C (p<0.001), in case of APGAR score. Key words: Maternal anaemia, gestational age, neonatal outcome, birth weight, APGAR score. DOI: http://dx.doi.org/10.3329/bjms.v10i3.8361 BJMS 2011; 10(3): 177-180